Self-Compassion and Forgiveness among Senior High School Students: A Correlational and Comparative Study: Array - Mungin Eddy Wibowo; Rohmatus Naini (Islamic Guidance and Counseling Journal, 2021)
The problem of low self-compassion and forgiveness in schools causes students to often feel stress and depression, blame themselves, and label themselves to do self-harm. The inability to accept oneself leads to the rejection of unpleasant experiences, failure, and imperfection. This study aims to examine the relationship between self-compassion and forgiveness among students at three Senior High Schools located in the City of Semarang, Indonesia. There were 178 students who were involved in this study with the age range from 14 to 17 years old. The authors used the self-compassion scale, which has 26 items by measuring six sub-aspects including self-kindness, self-judgment, common humanity, isolation, mindfulness, and over-identification. The author used 10 items of the trait forgiveness scale (TFS). The results showed that there is a positive relationship between self-compassion and forgiveness and showed no differences between self-compassion and forgiveness when viewed by gender.